Intellectual Property and Assessing its Financial Value : with a focus on life sciences - Sas, Benedikt (Chandos information professional series., 2014)
This book covers the different aspects, such as patents, trademarks and copyright of Intellectual Property (IP) from a more practical business perspective. Intellectual Property and Assessing its' Financial Value describes the differences between regions, mainly the differences between the US and EU. In addition, several tools are presented for assessing the value of new IP, which is of importance before engaging on a new project that could result in new IP or for licensing purposes. The first chapter introduces the different types of IP and illustrating the business importance of capturing an.